PENGARUH EFISIENSI BIAYA OPERASI (EBO), LIKUIDITAS, DAN ARUS KAS TERHADAP PROFITABILITAS PT. FASTFOOD INDONESIA TBK - Eka Sutisna; Fikriah; Darwis; Nawang Darmawan; Yusri, M Iqbal Yusri (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
The purpose of this study is to find out the effect of Operational Cost Efficiency (EBO), Liquidity, and Cash Flow on the Profitability of one of the restaurant subsector companies in Indonesia PT Fastfood Indonesia Tbk. This research is quantitative. The data collection techniques used in this study are library studies and documentation studies. The type of research data used is company secondary data in the form of annual financial statements from PT Fastfood Indonesia Tbk taken from the web official company, https://kfcku.com. The data is in the form of an annual company financial report from 2015-2020. From the test results obtained the result that the EBO had a negative and significant effect on Profitability, then Liquidity had a positive and insignificant effect on Profitability, while cash flow had a negative and insignificant effect on Profitability. Keywords: Operating Cost Efficiency (EBO), Liquidity, Cash Flow, Profitability